Laparoscopic Cholecystectomy, A single Surgeon experience at Teaching Hospital Biratnagar, Nepal (Journal of Nobel Medical College, 2017)
Background :Laparoscopic cholecystectomy (LC) is a treatment of choice for symptomatic gall stone disease and is commonly done all over the country in general surgical practice. The aim of this study is to show the results of LC in our medical college.Material and Methods: A retrospective analysis of the patients underwent laparoscopic cholecystectomy from July 2015 to September 2016 was carried out in NMCTH, Biratnagar. A total of 391 patients admitted through OPD of our Hospital underwent laparoscopic cholecystectomy were studied. All age groups and both sex were included.Results: Out of 391 patients with symptomatic cholelithiasis, 385(98.46%) patients underwent successful laparoscopic cholecystectomy. Age range of patients in the study varied between 12-84 years and maximum patients (30.69%) were found in the age group of 31-40 years. There were 333(82.58%) female and 58(17.41%)male patients. Mean age of the patients was 39.61 years. Indication for surgery was symptomatic cholelithiasis. Conversion was done in 6(1.53%) cases due to unclear anatomy. A rare congenital anomaly, Accessory right hepatic duct with cystic duct continuous with it was encountered in 12-yearboy; LC was done safely without injuring biliary tree. As postoperative complications, one patient developed biliary peritonitis which was managed by drainage tube.Conclusion: Laparoscopic cholecystectomy is successfully being done for last 5 years in our institute. The results are comparable with those of published series. Anatomical variations and complications may present, for which care must be taken. Journal of Nobel Medical CollegeVolume 6, Number 1, Issue 10 (January-June, 2017), page: 1-5